Productivity Shocks, Stabilization Policies and the Dynamics of Net Foreign Assets - Giorgio Di Giorgio; Salvatore Nisticò (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2011)
In this paper we investigate the role of macroeconomic stabilization policies for the international transmission of productivity shocks and their effects on the external sector. We develop a two-country stochastic Dynamic New-Keynesian 'perpetual youth' model of the business cycle with incomplete international financial markets. Our OLG structure implies stationary net foreign asset dynamics and allows for a thorough analysis of the interaction of monetary policy with non-balanced budget fiscal policy. We derive the dynamic and cyclical properties of fiscal deficit feedback rules and their implications for net foreign assets dynamics. Our results imply that the degree of 'fiscal discipline', i.e. the extent to which the fiscal rule responds to debt dynamics, is crucial for the dynamics of net foreign assets. We show that under a counter-cyclical fiscal rule with low fiscal discipline temporary positive productivity shocks may result in substantial deteriorations of the Net Foreign Asset position in the medium run. This result crucially hinges on the interplay among nominal rigidities, non-balanced budget fiscal policy, and the wealth effects on consumption that are implied by our OLG structure.
Keywords: E43; E44; E52; E58; 330; Fiscal Deficit; Net Foreign Assets; DSGE Models; Monetary and Fiscal Policy